Meneladani Karakter Lebah dalam Profesi Akuntan Manajemen - Sudarini; Tjiptohadi Sawarjuwono; Alfa Rahmiati (IPB University, 2023)
The pressure experienced by a management accountant tends to make him commit unethical behavior, especially financial report fraud. This causes a decrease in the quality of decision making by parties who have an interest in both management and third parties. This study used interpretive analysis and triangulation methods of in-depth interviews of a management accountant and observations who revealed that the characteristics of bees are hardworking, trustworthy, sincere and willing to sacrifice, disciplined, obedient and obedient, independent, not seeking positions, respecting leaders, beneficial to other beings. and maintaining cleanliness provides a handle for management accountants. The ethics of management accountants integrity, objectivity, competence and professional due care, confidentiality and professional behavior are in line with the character of bees. The bee characters used in this study come from Putra and Nurhadi, 2020, p. 139-192 and Jayana, 2016, p. 109-147.